Lipidomic analysis reveals altered lipid profiles of gingival tissues with periodontitis. (18th August 2022) - Zhou, Min; Li, Chen; Han, Xue; Yu, Bohan; Yan, Xiang‐zhen; Zhang, Yan; Yang, Xiao‐juan
Abstract: Aim: The role of lipids in periodontitis has not been well studied. Thus, this study aimed to explore periodontitis‐associated lipid profile changes and identify differentially expressed lipid metabolites in gingival tissues. Materials and Methods: Gingival tissues from 38 patients with periodontitis (periodontitis group) and 38 periodontally healthy individuals (control group) were collected. A ultra‐high performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry‐based non‐targeted metabolomics platform was used to identify and compare the lipid profiles of the two groups. The distribution and expression of related proteins were subsequently analysed via immunohistochemistry to further validate the identified lipids. Results: Lipid profiles significantly differed between the two groups, and 20 differentially expressed lipid species were identified. Lysophosphatidylcholines (lysoPCs), diacylglycerols (DGs), and phosphatidylethanolamines (PEs) were significantly up‐regulated, while triacylglycerols (TGs) were downregulated in the periodontitis group. Moreover, the staining intensity of ABHD5/CGI‐58, secretory phospholipase A2 (sPLA2), and sPLA2‐IIA was significantly stronger in the gingival tissues of patients with periodontitis than in those of healthy controls. Conclusions: LysoPCs, DGs, and PEs were significantly up‐regulated, whereas TGs were down‐regulated in gingival tissues of patients with periodontitis. Correspondingly, the immunohistochemical staining of ABHD5/CGI‐58, sPLA2, and sPLA2‐IIA in gingival tissues was consistent with the downstream production of lipid classes (lysoPCs, TGs, and DGs).